Debating Otherness with Richard Kearney : Perspectives from South Africa - Veldsman, Daniel; Steenkamp, Yolande; Steenkamp, Yolande (Durbanville AOSIS, 2018)
Richard Kearney is one of the leading global thinkers in both Continental philosophy and post-metaphysical philosophy of religion, as well as an esteemed Irish professor in philosophy, currently teaching at Boston College, Massachusetts, USA. Professor Kearney first visited South Africa in May as joint visiting academic of the Universities of Stellenbosch, Pretoria and North-West. The visit prompted the publication of this scholarly collected work, authored by South African and international scholars. These specialists in philosophy and religious studies analysed Kearney$1 (Bs influential work and brought his scholarly perspectives into dialogue with other leading thinkers in the field, both from Africa and abroad. This publication will be the first collective attempt to engage his work from the perspective of the African continent. This collected work contributes significantly in an interdisciplinary way to Ricoeurdian studies. The target audience of the book is peers and specialists in the field of Continental philosophy and philosophy of religion.s
English
Keywords: Philosophy: metaphysics & ontology; Philosophy of religion; Richard Kearney; anatheism; otherness; strangeness; transcendence; hermeneutics; hospitality; phenomenology; British idealism